2017
DOI: 10.1111/jog.13464
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hysteroscopic surgery for isthmocele associated with cesarean scar syndrome

Abstract: Aim: Cesarean scar syndrome (CSS) is characterized by increased risk of postmenstrual abnormal uterine bleeding, dysmenorrhea, and infertility, due to a post-cesarean scar defect known as an isthmocele. This study aimed to assess the impact of hysteroscopic surgery on isthmocele associated with CSS. Methods: Eighteen patients with CSS were enrolled. Surgical methods included resection of the inferior edge and superficial cauterization of the isthmocele via hysteroscopic surgery. We evaluated the residual myome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 8 publications
2
25
2
2
Order By: Relevance
“…The formation of scar diverticulum is an anatomical change, and surgical treatment may fundamentally solve the problem. Common surgical procedures include hysteroscopic electroresection of diverticular scars and electrocoagulation of the intima inside the diverticulum [6][7][8], laparoscopic or combined hysteroscopic and laparoscopic surgical resection of diverticular scar and uterus repair [9][10][11], and transvaginal surgical resection of scar and uterus repair [12,13]. Among these procedures, the combined hysteroscopic and laparoscopic surgical resection of scar and uterus repair method has been widely used in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of scar diverticulum is an anatomical change, and surgical treatment may fundamentally solve the problem. Common surgical procedures include hysteroscopic electroresection of diverticular scars and electrocoagulation of the intima inside the diverticulum [6][7][8], laparoscopic or combined hysteroscopic and laparoscopic surgical resection of diverticular scar and uterus repair [9][10][11], and transvaginal surgical resection of scar and uterus repair [12,13]. Among these procedures, the combined hysteroscopic and laparoscopic surgical resection of scar and uterus repair method has been widely used in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hysteroscopic is not recommended for patients with fertility needs [13]. But Tsuji et al [10] showed that due to fluid retention in PCSD, hysteroscopic resection and application of cauterization of inflammatory substances on PCSD surface will relieve internal pressure, promoting myometrial regeneration at PCSD, effectively increasing the thickness of the remaining myometrium and improving the lower uterine segment structure, all of which could be used to treat PCSD patients with fertility needs if their RMT is ≥2.5 mm. In hysteroscopic group, pregnancy rate was 56.2% (41/73).…”
Section: Discussionmentioning
confidence: 99%
“…The current two major surgical treatments of PCSD, hysteroscopy and combined hysteroscopic and laparoscopic, have been extensively compared for their advantages, disadvantages and efficacy [9,10]. However, which surgical modality is better for what kind of PCSD patients is still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…It showed that the mean thickness increased significantly from 2.1 mm before the resection to 4.2 mm after the surgery. 13 And since residual myometrial thickness of less than 2 mm is associated with a significant increase in the risk of uterine rupture, this technique should theoretically be associated with decreased possibility of a uterine rupture during subsequent trials of labor. 14,15 Similarly, the duration of menses after hysteroscopic treatment of isthmocele was shown to be significantly shorter from a mean of 12 days to 7.8 days along with a significant increase in patient satisfaction.…”
Section: Histologic Analysis Of the Scar Edges Usually Show Chronic Imentioning
confidence: 99%